2015
DOI: 10.3390/ma8115417
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Electroluminescence from Annealed-ZnO/GaN Heterojunction Light-Emitting Diodes

Abstract: This paper addressed the effect of post-annealed treatment on the electroluminescence (EL) of an n-ZnO/p-GaN heterojunction light-emitting diode (LED). The bluish light emitted from the 450 °C-annealed LED became reddish as the LED annealed at a temperature of 800 °C under vacuum atmosphere. The origins of the light emission for these LEDs annealed at various temperatures were studied using measurements of electrical property, photoluminescence, and Auger electron spectroscopy (AES) depth profiles. A blue-viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The near UV luminescence became the dominant emission with a broad green-yellow luminescence. As referred to the previous reports [23,29,[31][32][33], the native defect transitions in the n-ZnO and p-GaN layers, such as oxygen (V O ) and/or gallium (V Ga ) vacancies, could be responsible for the green-yellow emission, with a peak at around 520 nm. Moreover, it was noted that the peak of the near UV luminescence emerged from the DH-ZnO/p-GaN LED shifted to a shorter wavelength of 412 nm as compared to that of the n-ZnO/p-GaN heterojunction LED.…”
Section: Structurementioning
confidence: 65%
See 1 more Smart Citation
“…The near UV luminescence became the dominant emission with a broad green-yellow luminescence. As referred to the previous reports [23,29,[31][32][33], the native defect transitions in the n-ZnO and p-GaN layers, such as oxygen (V O ) and/or gallium (V Ga ) vacancies, could be responsible for the green-yellow emission, with a peak at around 520 nm. Moreover, it was noted that the peak of the near UV luminescence emerged from the DH-ZnO/p-GaN LED shifted to a shorter wavelength of 412 nm as compared to that of the n-ZnO/p-GaN heterojunction LED.…”
Section: Structurementioning
confidence: 65%
“…In the previous paper, Ho et al fabricated a n-ZnO/p-GaN-based LED that emitted broad near UV luminescence by optimizing the transparent electrode contact to the n-type ZnO [14]. The origin of the red, green-yellow, and blue-violet emission in the EL spectra from the n-ZnO/p-GaN-based LEDs annealed under various ambient to cause the interfacial diffusion, had also been discussed [22,23]. In addition, Zheng et al also fabricated an AlN-ZnO/ZnO/AlN-ZnO DH structure using the rf magnetron cosputtering technology.…”
Section: Introductionmentioning
confidence: 99%
“…Today ZnO is being deployed for applications such as gas sensors, solar cells, photodetectors, and liquid crystal displays [19][20][21]. Sensing, which is the target application in this study, has been one of the areas wherein ZnO has been found to be impactful [22][23][24]. However especially ethanol sensing using ZnO based nanostructures remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%